Dampak Teknologi Organisasi terhadap Transformasi Struktur dan Budaya Perusahaan : Sebuah Tinjauan Literatur - Handayani Handayani; Mela Candrika Putriana; Andhara Safa Lirani; Nurisma Kartika Dewi; Rauly Sijabat (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The development of information technology has had a significant impact on changes in the structure of modern organizations. Technology is no longer seen merely as a supporting tool but has become the core driver of business and operational transformation across various industries. This literature review provides a comprehensive discussion of how organizational technology influences structure, culture, and work processes within organizations, as well as the adaptive strategies employed to address the challenges of the digital era. Using a descriptive-qualitative approach, this study examines the role of technology in enhancing operational efficiency, strengthening cross-functional collaboration, and accelerating data-driven decision-making. Additionally, this research presents several implementation studies of technology in today's digital business landscape, offering a practical overview of the evolving dynamics. This discussion aims to serve as a reference for academics, practitioners, and organizations in understanding and strategically leveraging technology to achieve sustainable competitive advantage.